2015
DOI: 10.1080/08927022.2015.1089991
|View full text |Cite
|
Sign up to set email alerts
|

N-octane diffusivity enhancement via carbon dioxide in silica slit-shaped nanopores – a molecular dynamics simulation

Abstract: Equilibrium molecular dynamics simulations were conducted to study the competitive adsorption and diffusion of mixtures containing n-octane and carbon dioxide confined in slitshaped silica pores of width 1.9 nm. Atomic density profiles substantiate strong interactions between CO2 molecules and the protonated pore walls. Non-monotonic change in n-octane self-diffusion coefficients as a function of CO2 loading was observed. CO2 preferential adsorption to the pore surface is likely to attenuate the surface adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…However The effect of water on the dynamics of confined propane is similar to that reported at 300 K in an earlier publication 35 . However, the effect reported here is very different to that reported for CO2 on the dynamics of confined ethane 10 , propane 13 , butane 30 and octane 29 . CO2 was found to enhance the mobility of the confined hydrocarbons in all these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However The effect of water on the dynamics of confined propane is similar to that reported at 300 K in an earlier publication 35 . However, the effect reported here is very different to that reported for CO2 on the dynamics of confined ethane 10 , propane 13 , butane 30 and octane 29 . CO2 was found to enhance the mobility of the confined hydrocarbons in all these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In natural environments, however, pores are seldom occupied by a single species. While some studies have reported the effects of presence or absence of a second species on the dynamics of one guest 10,13,[27][28][29][30] , the most ubiquitous species that can be found in the natural pore environmentswater, has largely been ignored. Although the dynamics of confined water has been studied extensively 31,32 , the effect of water on the dynamics of another confined species remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we explored the effect of the pore surface morphology/roughness by inserting two step-edges along the Y-direction 31 (hence creating a structured pore). The step edges are chosen as examples of small defects on the pore surface.…”
Section: Resultsmentioning
confidence: 99%
“…Independent MD simulation studies have also confirmed that CO 2 enhances the diffusion of confined hydrocarbon. Le et al (2015Le et al ( , 2016 have shown that presence of CO 2 enhances the diffusivity of n-butane and n-octane in silica slit nanopores, by replacing the hydrocarbons from the pore walls thereby making them free to move through the pore network.…”
Section: Effect Of Co 2 On Dynamics Of Another Confined Volatilementioning
confidence: 99%